A conceptual paper on factors influencing financial institutions on lending technologies to technology-based SMEs in the northern region of Malaysia - Wan Sallha, Yusoff; Chuthamas, Chittithaworn; Noor Asliza, Abdul Rahim (Universiti Malaysia Perlis (UniMAP), 2010)
International Conference on the Roles of the Humanities and Social Sciences in Engineering (ICoHSE) 2010 organized by The Centre for Communication Skills and Entrpreneurship and The School of Business Inovation and Technopreneurship, Universiti Malaysia Perlis, 12th - 14th November 2010 at Bayview Beach Resort at Penang, Malaysia.